Circulating high sensitivity C reactive protein concentrations and risk of lung cancer: nested case-control study within Lung Cancer Cohort Consortium. (3rd January 2019) - Muller, David C; Larose, Tricia L; Hodge, Allison; Guida, Florence; Langhammer, Arnulf; Grankvist, Kjell; Meyer, Klaus; Cai, Qiuyin; Arslan, Alan A; Zeleniuch-Jacquotte, Anne; Albanes, Demetrius; Giles, Graham G; et al.
Abstract: Objectives: To conduct a comprehensive analysis of prospectively measured circulating high sensitivity C reactive protein (hsCRP) concentration and risk of lung cancer overall, by smoking status (never, former, and current smokers), and histological sub-type. Design: Nested case-control study. Setting: 20 population based cohort studies in Asia, Europe, Australia, and the United States. Participants: 5299 patients with incident lung cancer, with individually incidence density matched controls. Exposure: Circulating hsCRP concentrations in prediagnostic serum or plasma samples. Main outcome measure: Incident lung cancer diagnosis. Results: A positive association between circulating hsCRP concentration and the risk of lung cancer for current (odds ratio associated with a doubling in hsCRP concentration 1.09, 95% confidence interval 1.05 to 1.13) and former smokers (1.09, 1.04 to 1.14) was observed, but not for never smokers (P<0.01 for interaction). This association was strong and consistent across all histological subtypes, except for adenocarcinoma, which was not strongly associated with hsCRP concentration regardless of smoking status (odds ratio for adenocarcinoma overall 0.97, 95% confidence interval 0.94 to 1.01). The association between circulating hsCRP concentration and the risk of lung cancer was strongest in the first two years of follow-up for former and current smokers. Including hsCRP concentration in a risk model, in addition to smoking based variables, did not improve risk discrimination overall, but slightly improved discrimination for cancers diagnosed in the first two years of follow-up. Conclusions: Former and current smokers with higher circulating hsCRP concentrations had a higher risk of lung cancer overall. Circulating hsCRP concentration was not associated with the risk of lung adenocarcinoma. Circulating hsCRP concentration could be a prediagnostic marker of lung cancer rather than a causal risk factor.